Administration of Justice in Nigeria : Ideological Constraints and Allied Challenges (Strathmore Law Journal, 2025)
It is trite that the administration of the justice system in Nigeria is confronted by diverse challenges. Among the relatively better-known challenges are delays in the dispensation of justice by the courts, corrupt practices among judicial and law enforcement officers, disrespect of court judgments by the government, its agencies and other subjects, as well as the high cost of litigation. Perhaps one factor that may not be as apparent as other challenges is the jurisprudential ideology of positivism—inherited through the transportation of the British legal system into the country via the colonial relationship with Britain. The underpinning ideology influences and informs the judgments from the courts, which tend to translate to the dispensation of ‘technical’ or legalistic justice in linewith strict constructionist formats. To people traditionally attuned to a concept of justice rooted in the moral perception of fairness or good conscience, the technical nature of the justice emanating from the courts tends to raise questions and concerns as to the justness or equitability of such. Generally, these challenges and the nature of the Nigerian justice system erode the trust and confidence of the populace in the justice system, particularly the poor and less influential class’. Hence, this raises the question of whether Nigerian courts are the last hope of the common man. Against this background, this paper engages the discourse on the ideology, challenges and allied issues relating to the administration of justice in Nigeria.